Welfare Detection and Legal Effectiveness: Country Institutions Which the Authority is Regulated in Law in the Disputes of Authority - Demas Brian W; Sudarsono Sudarsono; Rachmad Safa’at; Muchamad Ali Safa’at (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Institutional design of the state with separation of powers and checks and balance give birth to the intersection of authority. This condition has the potential to create a power dispute between state institutions. Provisions regarding the resolution of disputes over state institutions are inseparable from issues concerning subjectum and objectum litis which have become jurisprudential and the institution is independent and is not subordinate to other institutions, so there are several state institutions that cannot resolve disputes in the Constitutional Court, namely state institutions that regulate them outside the Constitution, whether regulated by law or under the law. The purpose of this study is to describe the provisions of dispute resolution for the authority of state agencies which the authority is regulated in law. This journal research uses a qualitative paradigm with a phenomenological approach in the translation. The results obtained in this study are: 1) Detection of  Welfare which will be realized in maximum when all state agencies effective in operation; 2) Paradigm: Analysis of Dispute Authority of State Institutions. On the basis of a modern legal state, disputes over the authority of state institutions that are formed based on the law, need to be channeled to settle so that they remain based on due process of law and there are no rules in the process of resolving disputes over the authority of state institutions in the law.